Association Between Overnutrition Status and Work Productivity Among Workers in Indonesia: A Systematic Literature Review and Meta-Analysis - Muhammad Jagad Pramundito; Annisa Nuradhiani; Ratu Diah Koerniawati (Universitas Tribhuwana Tunggadewi, 2026)
Overnutrition, including overweight and obesity, has emerged as a growing public health concern that may adversely affect workers’ health status, physical capacity, and overall job performance. In Indonesia, the prevalence of overweight and obesity among adults continues to increase, potentially contributing to reduced labor productivity. However, empirical findings on the relationship between nutritional status and work productivity among Indonesian workers remain fragmented and inconsistent across individual studies. Therefore, this study aimed to synthesize existing evidence and examine the association between over nutritional status and work productivity among workers in Indonesia through a systematic literature review and meta-analysis. A comprehensive literature search was conducted in Google Scholar, Semantic Scholar, Scopus, and Web of Science using the PICOS framework. Eligible studies were quantitative cross-sectional studies published between 2015 and 2025 that assessed body mass index (BMI) and work productivity among Indonesian workers. Statistical synthesis was performed using a random-effects meta-analysis model with odds ratios (ORs) and 95% confidence intervals (CIs) as the effect measures. A total of 20 studies met the inclusion criteria and were included in the quantitative analysis. The pooled results demonstrated that workers with abnormal nutritional status had significantly higher odds of experiencing reduced work productivity compared to workers with normal nutritional status (OR = 2.20; 95% CI: 1.19–4.08; p = 0.0001), with moderate heterogeneity across studies (I² = 64%). These findings suggest that overnutrition represents an important determinant of work productivity among Indonesian workers and highlight the need for workplace-based nutrition and health promotion interventions to support workforce performance and sustainability.